How involvement in COVID-19-related work changed nurses' job demands, job resources, and their associations with burnout: Evidence from China - Wang, X.; Ma, S.; Liao, W. (OBM Neurobiology, 2023)
China adopted a “Zero-COVID” policy for nearly three years, making Chinese healthcare workers constantly involved in COVID-19-related work. However, little is known about how involvement in COVID-19-related work shaped Chinese nurses’ burnout. This study explores how nurses’ job demands and job resources are associated with their burnout by considering high and low frequent involvements in COVID-19-related work in China. This study employed a cross-sessional design. Guided by Job Demands-Resources (JDR) model, we developed hypotheses and tested them using regression analysis with a sample of 336 nurses working in four public hospitals in Guangdong, China. Overall sample results revealed: 1) frequency of involvement in COVID-19-related work was related to a higher level of workload; 2) nurses’ burnout was positively associated with workload, emotional demands, and work-family conflict, and negatively associated with a relationship with supervisor, remuneration, and independence of work; 3) emotional intelligence mitigated the positive relationship between workload and burnout. Comparison analysis showed significant differences due to the frequency of involvement in COVID-19 work. In the high-frequency group (N = 108), 1) emotional demands were related to a higher level of burnout, and emotional intelligence moderately accentuates the positive relationship between the two variables; 2) remuneration was related to a lower level of burnout; 3) nurses reported higher levels of workload and relationship with the supervisor. In the low-frequency group (N = 147), independence of work was related to a lower level of burnout; We found some evidence that nurses’ job demands and job resources and their associations with burnout differed due to their frequency of involvement in COVID-19-related work. Implications for policy-making and theoretical contribution are discussed.